Development and Application of an Integrated Index for Occupational Safety Evaluation - Paulo Silva; Mariana Carneiro; Nélson Costa; Isabel Loureiro; Paula Carneiro; Abel Pires; Cátia Ferreira (Safety)
Occupational safety, reflecting the likelihood of work-related accidents, is crucial in work systems. A risk management model identifies, analyzes, and prioritizes risks, followed by the strategic application of resources to mitigate, monitor, and control the probability and impact of future events. Models integrating safety, ergonomics, and operational efficiency in risk management are non-existent, especially in the food retail sector. The proposed risk management model assigns the risk level to Safety using the Hazard Identification and Risk Assessment index (HIRA), an integral part of the Global Safety Index (GSI), both indices with five risk levels: 1 to 5 (acceptable to very critical). The organizational hierarchy of the evaluated company includes levels from microtask to insignia. The research aims to apply the HIRA index from the microtask to the area level. The HIRA application was conducted in a food retail company, starting with the identification and characterization of tasks in the “food” section and “fresh products” area (butchery, fishmonger, bakery, charcuterie/takeaway, and fruits and vegetables sections). The risk level of each microtask was assessed, then aggregated to higher organizational levels. Results showed that two new solutions reduced the safety risk in the mentioned sections proving the HIRA value as decision-making tool.